DEFINITION AND INTERPOLATION OF DISCRETE METRIC FOR MESH GENERATION ON 3D SURFACES - Głut, Barbara; Jurczyk, Tomasz (Computer Science, 2013)
The article concerns the problem of a deﬁnition of the control space from a set of discretedata (metric description gathered from diﬀerent sources) and its inﬂuence on the eﬃciency ofthe generation process with respect to 2D and 3D surface meshes. Several methods of metricinterpolation between these discrete points are inspected, including an automated selectionof proper method. Some aspects of the procedures of creation and employment of the meshcontrol space based on the discrete set of points are presented. The results of using diﬀerentvariations of these methods are also included.